Adhesive and alloying properties of dual purpose polyfurfuryl alcohol binder for binder jet additive manufacturing of steel - Tan, Wei Xin (2024)
In-situ alloying in steel can be achieved in the binder jet additive manufacturing process by incorporating alloying elements into the binder. However, using binders with nanoparticle suspensions often leads to challenges with particle dispersion uniformity and nozzle clogging. To circumvent these limitations, we investigated the feasibility of using a particle-free binder based on poly(furfuryl alcohol) (PFA) for binder jet 3D printing of steel. The PFA binder serves dual purposes – (i) imparting structural integrity to the as-printed green part and (ii) providing carbon upon pyrolysis to alloy the printed iron parts into steel. The PFA binder was first dispensed layer-by-layer into a low alloy steel powder bed to produce green parts with a storage modulus of 3360 MPa and a compressive strength of up to 9 MPa. Compared to the control, a commercial carbon binder ink, the present particle-free PFA formulation offered better green part rigidity (+18 %) and strength (+18.5 %) for the same amount of carbon alloying. The green parts were then subjected to debinding and sintering to consolidate the steel powder particles. During vacuum sintering, the PFA was pyrolyzed and left behind a carbon residue which diffused into the steel part to form a hard and strong ferrite-carbide aggregate phase that significantly enhanced the hardness, yield strength and ultimate tensile strength of the sintered steel parts. Furthermore, by varying the amount of this particle-free binder formulation at different locations, components with site-specific microstructures and mechanical responses, confirmed through hardness tests and digital image correlation, were also demonstrated.